A green emitting (Ba, Ca)ScO2F:Bi3+, K+ perovskite phosphor with high efficiency and good thermal stability for LED backlight displays. Issue 15 (24th June 2022) - Cai, Mingsheng; Lang, Tianchun; Han, Tao; Valiev, Damir; Fang, Shuangqiang; You, Houjiang; Liu, Bitao; Du, Ling; Xu, Zichao; Polisadova, Elena F.
Abstract : A new efficient green-emitting (Ba, Ca)ScO2 F:Bi 3+, K + phosphor realizes a high color gamut of 110% of the NTSC value under 415 nm chip excitation. Abstract : Investigating narrow-band green emitting phosphors with high efficiency and good thermal stability is the main goal of the present light-emitting diode (LED) display research. Here, Ba1− x Ca x ScO2 F:0.001Bi 3+, 0.001K + ( x = 0–0.12) perovskite phosphors, emitting narrow green light excited by a 415 nm chip, were developed using the cation substitution design strategy. The effects of Ca 2+ substitution for Ba 2+ in the Ba1− x Ca x ScO2 F:0.001Bi 3+, 0.001K + crystal structures and photoluminescence properties were investigated. All the phosphors show the cubic perovskite-type structure in the space group Pm 3 m . The evolution of the cell parameters and the Ba/Ca/K/Bi–O bond lengths were evaluated. The phosphors with the internal quantum efficiency of 77.4% exhibit bright green emission peaking at 510 nm under 415 nm chip excitation. The improvement of luminescence efficiency and thermal stability was discussed in detail in relation to the local structure variation. The cation substitution design strategy mentioned here can become an important approach to realize the spectral modulation through controlling the micro-environment in the lattice for excellent LED backlight displays.